2011 IEEE International Conference on Mechatronics and Automation 2011
DOI: 10.1109/icma.2011.5986241
|View full text |Cite
|
Sign up to set email alerts
|

Study on error sensibility of UPU parallel manipulator based on probability distribution

Abstract: This paper takes the 3-UPU parallel manipulator which possesses 3 translational and 1 revolute (3T1R) motions as a studying case. The sensitivity of degree of freedom (DOF) characteristics and kinematic errors resulting from various kinds of torsion angle errors is observed. Kinematic model of the manipulator is established and typical torsion angle errors are enumerated. Based on the model and particular probability distribution, forward solutions are solved and discussed in two cases by numerical method. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Kiper and Söylemez [58] showed that when the base and the moving platform of the PM are identical, the PM has 4-DoF and furthermore, it has a finite singularity mode with 5-DoF when the limb lengths are the same. Guo et al [59] investigated the position and orientation errors of the PM.…”
Section: Introductionmentioning
confidence: 99%
“…Kiper and Söylemez [58] showed that when the base and the moving platform of the PM are identical, the PM has 4-DoF and furthermore, it has a finite singularity mode with 5-DoF when the limb lengths are the same. Guo et al [59] investigated the position and orientation errors of the PM.…”
Section: Introductionmentioning
confidence: 99%